Epidemiological and virological characteristics of respiratory tract infections in children during COVID-19 outbreak - Zhu, Yueling (BMC Pediatr, 2021)
BACKGROUND: To investigate the impact of protective measures and isolation on respiratory tract infections in children during the COVID-19 outbreak. METHODS: We extracted data on outpatient visits and respiratory infection visits, and tests of respiratory viruses (adenovirus (ADV), influenza A (FluA), influenza B (FluB) and respiratory syncytial virus (RSV)) from electronic healthcare records in Children’s Hospital, Zhejiang University School of Medicine during the COVID-19 outbreak (January–April, 2020), compared with those in 2018 and 2019 during the same periods. RESULTS: We found that outpatient visits in January, 2020 was comparable with those in 2018 and 2019, but decreased by 59.9% (288,003 vs. 717,983) and 57.4% (288,003 vs. 676,704), respectively during the period of February-April, 2020, as compared with the same periods in 2018 and 2019. The total number of respiratory tract infections from January to April 2020 decreased by 65.7% (119,532 vs.348,762) and 59.0% (119,532 vs.291,557), respectively compared with the same periods in 2018 and 2019. The proportion of respiratory tract infections during the outbreak also dropped compared with the same periods in 2018 and 2019 (P<0.001). We also found significantly decreased number of completed tests for respiratory viruses and positive cases of ADV, FluA, FluB, and RSV during February-April, 2020. CONCLUSIONS: In this study, we found that outpatient visits and respiratory tract infections in children significantly decreased during COVID-19 outbreak. Adequate protective measures and isolation in children may help to prevent respiratory virus infections in children.